Conceptualising non-state security - Brailey, TJ (2024)
Why do states choose to engage with non-state security apparatuses when faced with domestic threats? This research tackles two distinct challenges. First, I seek to understand how non-state security actors are organized and how they operate. Second, I assess the circumstances under which developing states choose to outsource their coercive capabilities to non-state security actors as opposed to their own militaries or other state militaries. I answer these puzzles using a novel dataset on non-state security actors, their characteristics, and their operations. I identify four latent clusters of non-state security actor using unsupervised machine learning techniques. Using this typology, I develop a theory of why states might choose to engage with different forms of non-state security, testing these theories with a number of prediction models. I find suggestive evidence that states with low levels of military diversity are more likely to outsource their coercive powers to non-state security actors who provide multiple services across multiple domains, essentially serving as a surrogate army for a lower cost. Implications are studied and discussed using a comparative case study of four non-state security actors.